2002
DOI: 10.1073/pnas.032488499
|View full text |Cite
|
Sign up to set email alerts
|

HemK, a class of protein methyl transferase with similarity to DNA methyl transferases, methylates polypeptide chain release factors, and hemK knockout induces defects in translational termination

Abstract: HemK, a universally conserved protein of unknown function, has high amino acid similarity with DNA-(adenine-N6) methyl transferases (MTases). A certain mutation in hemK gene rescues the photosensitive phenotype of a ferrochelatase-deficient (hemH) mutant in Escherichia coli. A hemK knockout strain of E. coli not only suffered severe growth defects, but also showed a global shift in gene expression to anaerobic respiration, as determined by microarray analysis, and this shift may lead to the abrogation of photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
118
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 32 publications
3
118
0
Order By: Relevance
“…Within this superfamily, nucleic acid MTases belong to two distinct clades, one including all nucleic acid C5 MTases 58 and the other uniting enzymes catalyzing methylation of both N 4 C and N 6 A, those modifying the N2 position of guanines in RNA, as well as certain protein MTases methylating the amide group of glutamine in proteins such as the ribosomal protein L3 and peptide release factors (HemK family) 59, 60, 61. Members of the latter clade are characterized by a [DNSH]PP[YFW] motif at the C‐terminus of conserved strand‐4 of the Rossmann domain 18, 20, 21, 62 (Fig.…”
Section: Anatomy Of N6a‐mtases‐mtase Domainsmentioning
confidence: 99%
“…Within this superfamily, nucleic acid MTases belong to two distinct clades, one including all nucleic acid C5 MTases 58 and the other uniting enzymes catalyzing methylation of both N 4 C and N 6 A, those modifying the N2 position of guanines in RNA, as well as certain protein MTases methylating the amide group of glutamine in proteins such as the ribosomal protein L3 and peptide release factors (HemK family) 59, 60, 61. Members of the latter clade are characterized by a [DNSH]PP[YFW] motif at the C‐terminus of conserved strand‐4 of the Rossmann domain 18, 20, 21, 62 (Fig.…”
Section: Anatomy Of N6a‐mtases‐mtase Domainsmentioning
confidence: 99%
“…With this connection to translational RFs, the knowledge of the methylation modification of these factors, and sequence similarities of HemK with methyltransferases, they were able to put all of the pieces together. In their article, they clearly show that mutants in hemK lack the modification of the glutamine residue in both RF1 and RF2 and that the HemK protein is sufficient to catalyze the methylation reaction in vitro (1). So, how can one now rationalize the original heme-defective phenotype seen?…”
mentioning
confidence: 99%
“…This issue of PNAS presents an article by Nakahigashi et al (1) that shows how a gene product originally identified by its mutant phenotype as an enzyme of heme biosynthesis and then by sequence similarity as a possible DNA adenine-N-6-methyltransferase actually functions as a protein glutamine methyltransferase modulating the termination activity of release factors (RFs) in ribosomal protein synthesis! It provides a nice case study for why one can't rest until the biochemistry is done.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in E. coli, HemK/PrmC is thought to methylate the conserved glutamine residue within the translation release factors RF-1 and RF-2 (SGAGGQHVN) to terminate protein synthesis efficiently (Nakahigashi et al, 2002). In contrast to this permanent methylation, the glutamine residue within the cytoplasmic domains of transmembrane chemoreceptors is methylated by CheR and demethylated by CheB (Kehry and Dahlquist, 1982).…”
Section: Methylation and All0012mentioning
confidence: 99%